Angle resolver X-ray photoelectron spectroscopic analysis of the passive film of the corrosion-resistant W-32Zr alloy in 12 M HCl solution - Bhattarai, Jagadeesh (Bangladesh Journal of Scientific and Industrial Research, 2015)
The sputter-deposited amorphous W-32Zr alloy was passivated spontaneously and showed a fairly high corrosion resistance in 12 M HCl solution in open air at 30°C. The average corrosion rate of the W-32Zr alloy (i.e., 5.2 × 10-3 mm/y) was found to be lower than those of alloy-constituting tungsten and zirconium elements. Such synergistic effects of simultaneous addition of tungsten and zirconium in the W32Zr alloy was investigated by corrosion tests, electrochemical measurements and angle resolved X-ray photoelectron spectroscopic (ARXPS) analyses. High corrosion resistance of the binary W32Zr alloy is mostly due to the formation of homogeneous passive oxyhydroxide film consisting of Wox and Zr4+ cations with a small concentration gradient indepth from ARXPS analysis. Consequently, zirconium metal acts synergistically with tungsten in enhancing the anodic passivity as well as the corrosion resistance properties of the sputterdeposited W32Zr alloy in 12 M HCl solution open to air at 30°C. DOI: http://dx.doi.org/10.3329/bjsir.v49i2.22004 Bangladesh J. Sci. Ind. Res. 49(2), 103-110, 2014